RENCANA PENDIRIAN BISNIS BARU CUCI MOBIL “JOJO’S CLEAN” - Joshua Radityo Adiwijaya; Christiana Fara Dharmastuti (Prosiding Working Papers Series In Management, 2018)
Jojo's Clean "car washing business is a car washing business with the vision of" Makes the fastest car wash business that prioritizes customer satisfaction and convenience ". Jojo's Clean car wash business has the concept of "Quick clean" where customers can wash the car in just 15-20 minutes. Car wash process in Jojo's Clean is more safety than conventional car wash business, because it does not use hydraulics to minimize the fall of the car from the hydraulic top due to broken hydraulic rod. The car wash process is carried out by directing the customer's car coming to the washing spot that has been provided, then it will be cleaned by "Jojo's Clean" employees and rinsed using a rinse machine. After the flushing stage, then the customer's car was directed to the parking lot that has been provided for drying. The price is set for a car wash of Rp 50,000 per car and the initial capital needed to set up this business is Rp 585,000,000. Based on the results of the business feasibility analysis, the NPV generated amounted to Rp 898,959,050, the payback period was estimated for 3 years 3 months 6 days, and the profitability index generated by 3.05. Keywords : car wash process, Cibubur and its surrounding, fastest car wash business, middle and upper society, Cibubur and its surroundings, quick clean.